GE14 : Will Urban Malays Support Pakatan Harapan? - Saiful Wan Jan, Wan (Trends in Southeast Asia ;, 2019)
In Malaysia's last general election, urban voters tended to support the opposition coalition -- 72 of the 97 urban parliamentary seats were in fact won by it. However, most of these seats have a mixed demography, with a high percentage of ethnic Chinese voters. In the upcoming general election, Pakatan has a good chance of winning the federal government if Malay voters join their Chinese counterparts in supporting the opposition coalition. A subsequent so-called "Malay tsunami" could lead to a Pakatan victory. This present study, which is based on a series of focus group discussions held in the Malaysian states of Kedah and Johor, finds that urban Malay voters are very unhappy with the economic condition of the country and are also worried about corruption. But despite their grouses, they are still uncertain about supporting the opposition coalition due to the fear of losing the race-based privileges they enjoy as ethnic Malays.